Production of seedlings of Anadenanthera peregrina in response to alternative substrates with cane bagasse - Massad, Marília Dutra; Dutra, Tiago Reis; Cardoso, Rafaela Letícia Ramires; Santos, Tiago Barbosa; Sarmento, Mateus Felipe Quintino (Revista Ecologia e Nutrição Florestal - ENFLO, 2016)
This study aimed to evaluate the influence of different particle sizes of sugar cane bagasse for composition of alternative substrates made from a mixture of a commercial substrate, in the production of red angico seedlings (Anadenanthera peregrina). The experiment was conducted in a randomized block design with three replications, in a factorial scheme (5 x 2), five substrates (100% Rohrbacher®, 75% Rohrbacher® + 25% sugar cane bagasse (75R + 25BC); 50% Rohrbacher® + 50% sugar cane bagasse (50R + 50BC), 25% Rohrbacher® + 75% sugar cane bagasse (25R + 75BC), 100% sugar cane bagasse) and two particle sizes (4 mm and 6 mm). We evaluated the shoot height (H); the Diameter Collect (DC); the Shoot Dry Mass (SDM); the Root Dry Mass (RDM) and Total Dry Mass (TDM), and the relationship H / DC, H / SDM, SDM / RDM and DQI (Dickson Quality Index). The substrates size of substrates 1 (past 4 mm sieve) provided higher germination rate of the seeds of red angico, height gain and H / DC seedlings of the species. Alternative substrates 75R + 25BC, 50R + 25R + 50BC and 75BC, besides the commercial substrate Rohrbacher®, showed potential for use in the production of red angico seedlings.